1945
DOI: 10.1021/ja01224a003
|View full text |Cite
|
Sign up to set email alerts
|

Absorption Spectra of Certain α,β-Unsaturated Ketones, including Benzal Compounds

Abstract: Absorption Spectra of «.^-Unsaturated Cyclic Ketones 1230 trated sulfuric acid and fractionally distilled from metallic sodium.Cyclopentanols.-1-Propylcyclopentanol, m. p. -17.0°, b. p. 72°at 12 mm., d2\ 0.9046, »íod 1.4538, and 1-isopropylcyclopentanol, m. p. 21-22°, b. p. 70°at 15 mm., d"< 0.9135, w"d 1.4560, were prepared, dehydrated over iodine and hydrogenated by standard procedures.A solution of 63 g. of 1-propylcyclopentanol in 70 g. of absolute ethanol was hydrogenated directly to propylcyclopentane ov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

1948
1948
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Indeed, in such a structure neither the ESIPT nor the reketonization mechanisms dominating the decay dynamics of all the previously evaluated keto-enolic curcuminoids can take place. We were able to find only a few papers dedicated to the chemistry of cyclopentanones and cyclohexanones, in which the spectral and intramolecular charge distribution properties of either CYV or chemically related compounds are investigated [41,42,43,44,45]. However, it is established that CYV conserves many of the most significant ground-state biological properties of CURC, including the anti-inflammatory ( i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, in such a structure neither the ESIPT nor the reketonization mechanisms dominating the decay dynamics of all the previously evaluated keto-enolic curcuminoids can take place. We were able to find only a few papers dedicated to the chemistry of cyclopentanones and cyclohexanones, in which the spectral and intramolecular charge distribution properties of either CYV or chemically related compounds are investigated [41,42,43,44,45]. However, it is established that CYV conserves many of the most significant ground-state biological properties of CURC, including the anti-inflammatory ( i.e.…”
Section: Introductionmentioning
confidence: 99%
“…The cyclopropyl group may be considered a chromophore but weaker than an ethylenic bond, since in cyclopropane the bonds are under less strain. This viewpoint (15,63,78,193) is supported by the fact that the color deepens in going from cyclohexane to cyclopropane and also for the series cyclohexanone, cyclopentanone, cyclobutanone, and ketene (20,89,93). In this connection a number of studies (61, 109, 155, 200a, 257a) have shown that the cyclopropyl ring and the epoxy group have chromophoric powers approaching that of an ethylenic bond.…”
Section: ±<^==^>=Ch-n=n-ch=<^)=fmentioning
confidence: 89%
“…After studying a number of ,/3-unsaturated carbonyl compounds, Woodward (307) found that the values of Xmax for such compounds can be approximated in Evans and Gillam (81,82,98) and other investigators (14,93,300) have measured the spectra of many ,/3-unsaturated ketones and aldehydes and found additional evidence to substantiate Woodward's table. However, Evans and Gillam found that the aldehydes have a Xmax only 5 µ lower than that of the corresponding ketones, rather than 10 µ.…”
Section: B Aß-umaturated Carbonyl Compoundsmentioning
confidence: 93%
“…The stability of these intermediates was examined using UV absorption spectra (18,19) and voltammetric data (18,(20)(21)(22) in the different media. To understand the influence of the solution medium on reactivity, a newly improved method developed by our group (23,24) was used to determine the adsorption strength by evaluating Henry constants.…”
Section: Introductionmentioning
confidence: 99%